1997
DOI: 10.1046/j.1365-2494.1997.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and yield components as affected by forage removal in winter and spring triticale

Abstract: Two field experiments were carried out under irrigation and high fertility in northeastern Spain during 1992 and 1993. Ten triticale genotypes, five of spring growth habit and five winter types, were tested for their suitability for both forage and grain. Forage removal reduced grain yield per plant by about 17%, but did not have any significant effect on plant density, ear density or tiller number per plant. Tiller mortality was greater in winter types (65%) than in spring triticales (25%), but was not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…However, significant direct effects were revealed by the path coefficient analysis in all environments. Nevertheless, correlation and path coefficients analysis showed that kernel weight had the major effect on grain yield under cooler irrigated conditions, as found in previous works in the region (Royo, 1997; Royo and Tribó, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…However, significant direct effects were revealed by the path coefficient analysis in all environments. Nevertheless, correlation and path coefficients analysis showed that kernel weight had the major effect on grain yield under cooler irrigated conditions, as found in previous works in the region (Royo, 1997; Royo and Tribó, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Here in Experiment 2, the two groups were sown too far apart (due to surface moisture conditions) or in Experiment 3 were sown on the same date, so key development phases did not coincide. Our results here add to many other studies that have found both different and similar responses to defoliation across wheat genotypes varying in their phenological development (Royo and Romagosa, 1996;Royo, 1997;McMullen and Virgona, 2009;Sprague et al, 2018). This lack of consistency suggests this is a problematic relationship to unravel experimentally as it is very difficult to isolate the environmental conditions from genotypic effects and their interactions.…”
Section: Genotype Effects On Grain Yield Response After Defoliationsupporting
confidence: 59%
“…However, relatively little has been done to understand the dynamics of regrowth and physiological factors and processes involved in recovery after grazing in different genotypes (Harrison et al, 2011b,c). Some experiments have found larger trade-offs between grazing and grain yield for spring cultivars than in slowerdeveloping winter cultivars (Sprague et al, 2018), while others have found similar responses in winter and spring types (Royo and Romagosa, 1996;Royo, 1997). Taller genotypes have been found to have less yield reduction from grazing than newer semidwarf cultivars, due to differences in susceptibility to lodging and yield potential (Winter and Thompson, 1990), but differences in growth habit amongst semi-dwarf genotypes (erect vs. prostrate) were not shown to differ in response to defoliation (Butchee and Edwards, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, genotypic variability for the maximum length of the first tiller stem seems to be due more to the different tillering strategy of spring and winter triticale types than to phenology. The length of the first tiller was closer to the length of the main stem in winter types than in spring types, which supports the assumption of tillers playing a greater role in the yield formation in winter types than in spring types (Royo, 1997). The patterns of biomass (CDW) accumulation of spring and winter triticale were similar.…”
Section: Variabletsupporting
confidence: 73%